2013
DOI: 10.1007/s10554-013-0186-x
|View full text |Cite
|
Sign up to set email alerts
|

Early renal dysfunction after contrast media administration despite prophylactic hydration

Abstract: The actual incidence of renal dysfunction after contrast media administration seems to be underestimated, especially in the context of epidemiological data. There are only few data concerning the monitoring of impaired kidney function within a few hours after iodine contrast medium application. Hence, the purpose of this study is to observe the incidence of early renal function deterioration within 12–18 h after administration of iodine contrast media in patients scheduled for elective coronary angiography, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…CIN is defined as the impairment of renal function manifested by an increase of creatinine of 0.5 mg/dl or 25% from baseline within 48–72 h post-contrast administration ( 7 , 11 , 12 ). In the present study, early CIN was defined as fulfilling the CIN criteria definition at 6–10 h post-contrast administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIN is defined as the impairment of renal function manifested by an increase of creatinine of 0.5 mg/dl or 25% from baseline within 48–72 h post-contrast administration ( 7 , 11 , 12 ). In the present study, early CIN was defined as fulfilling the CIN criteria definition at 6–10 h post-contrast administration.…”
Section: Methodsmentioning
confidence: 99%
“…Early recognition of contrast-induced acute kidney injury is of high clinical importance especially with the short hospitalization time currently employed for patients scheduled for CA or intervention. Previously, early renal dysfunction was reported to occur only a few hours post-CA ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the paper by Burchardt et al [2] the authors investigated the incidence of early renal function deterioration within 12-18 h after the administration of iodine contrast media in patients scheduled for elective coronary angiography, who were intravenously and orally hydrated. This was a singlecenter retrospective analysis in a total of 319 patients enrolled over a period of 16 months.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…Major advances in recent years have been reduction of radiation and contrast media exposure. Several related manuscripts have been published in the journal: Burchardt et al [72] examined the incidence of early renalfunction deterioration within 12-18 h after administration of iodine contrast media in 319 patients, scheduled for elective coronary angiography, who were intravenously and orally hydrated. The data suggest that early deterioration of renal function may occur in 13-28 % of all patients.…”
Section: Computed Tomographymentioning
confidence: 99%
“…1 Contrastinduced nephropathy is conventionally defined as an elevation of serum creatinine (sCr) level by 25% or higher or 0.5 mg/dL or greater (44 μmol/L) from baseline within 48 hours after a diagnostic or interventional procedure in the absence of an alternative etiology. [2][3][4] However, previous studies demonstrated that sCr was not an ideal indicator of CIN, especially in subjects with normal sCr at baseline, which is an intrinsic flaw of sCr so-called creatinine blind range. 3,[5][6][7] Cystatin C, a cysteine protease inhibitor (molecular weight, 13.3 kd) that has a constant production rate irrespective of muscle mass and a plasma concentration determined by glomerular filtration alone, is considered to be a more sensitive predictor of CIN when compared with sCr.…”
mentioning
confidence: 99%